On $R$-$(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a new class of functions between bitopological spaces called $R$-$(τ_1,τ_2)$-continuous functions. Furthermore, several characterizations and some properties concerning $R$-$(τ_1,τ_2)$-continuous functions are established.